2019
DOI: 10.1097/sap.0000000000001770
|View full text |Cite
|
Sign up to set email alerts
|

Graciloplasty for Anal Incontinence—Is Electrical Stimulation Necessary?

Abstract: Introduction Anal incontinence brings lot of social embarrassment, mental distress, dignity loss, anxiety, low confidence, and eventually a low self-esteem with a restricted social life to the affected person. Surgical repair is the mainstay of treatment for anal incontinence. However, some patients need additional procedures such as gluteoplasty, graciloplasty (adynamic and dynamic), artificial bowel sphincter, and sacral nerve stimulation, which help to reinforce or augment the anal sphincter. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…In the past, electrostimulation is commonly used after the graciloplasty to transform the gracilis muscle from type II to type I (slow-twitching fatigue-resistant fibers), which allows the gracilis muscle to work as a new sphincter and maintain a sustained contraction. 7 However, in most of these cases, they only achieved partial continence at best, with continued fecal leakage requiring diapers still. The success of conventional graciloplasty has been less than 50% mainly due to muscle fatigue and the inability of patients to voluntarily contract the transposed muscle.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the past, electrostimulation is commonly used after the graciloplasty to transform the gracilis muscle from type II to type I (slow-twitching fatigue-resistant fibers), which allows the gracilis muscle to work as a new sphincter and maintain a sustained contraction. 7 However, in most of these cases, they only achieved partial continence at best, with continued fecal leakage requiring diapers still. The success of conventional graciloplasty has been less than 50% mainly due to muscle fatigue and the inability of patients to voluntarily contract the transposed muscle.…”
Section: Discussionmentioning
confidence: 98%
“…Gohil et al described the use of a single gracilis muscle wrapped around the anus in an “alpha,” “epsilon,” and “gamma” configuration, and showed that satisfactory continence was achieved in 76.4% of the patients in adynamic gracilis reconstruction. 7 The disadvantage of wrapping around the anus completely, was that it would exert a pulley effect, where the resultant force generated is centrifugal and could not collapse the anus to enforce continence. Rouanet et al used a gamma configuration for each gracilis muscle, and fixed both muscles to each other to create a double gracilis wrap.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, electrostimulation is commonly used after the graciloplasty to transform the gracilis muscle from type II to type I (slow-twitching fatigue-resistant bers), which allows the gracilis muscle to work as a new sphincter, and maintain a sustained contraction [7]. However, in most of these cases, they only achieved partial continence at best, with continued faecal leakage requiring diapers still, The success of conventional graciloplasty has been less than 50% mainly due to muscle fatigue and the inability of patients to voluntarily contract the transposed muscle 5 .Gohil et al described the use of a single gracilis muscle wrapped around the anus in a "alpha", "epsilon", and "gamma" con guration, and showed that satisfactory continence was achieved in 76.4% of the patients in adynamic gracilis reconstruction [7]. Rouanet et al used a gamma con guration for each gracilis muscle, and xed both muscles to each other to create a double gracilis wrap.…”
Section: Discussionmentioning
confidence: 99%
“…This induces contractions, and the initial fast-twitch fatigable muscle is retrained to become a slowtwitch, fatigue-resistant muscle. The technique demonstrated good effect in some patients, but complications were common [56][57][58]. Complications included surgical site infection, pain, device problems, erosion, and outlet obstruction.…”
Section: Gracilis Muscle Transpositionmentioning
confidence: 99%